THE "MONOTRIBUTO" REGIME AND THE WORKER COOPERATIVES IN ARGENTINA: THE DIVERSIFICATION OF A FISCAL POLICY. - Torres, Miguel Agustin (International Journal of Cooperative Law, 2025)
The “monotributo”, implemented in 1998, with the creation of the “Simplified Regime for Small Taxpayers” by National Law 24977, is the main tax option that the Argentine tax system offers to the members of worker cooperatives. Designed with a predominantlyfiscal purpose, the regime has undergone significant transformations over the years.In this paper we try to characterize, from a legal perspective, the “monotributo” regimein the Argentine legal system, describing the main changes that it has experienced since its implementation and addressing the underlying reasons for them.